Probing the topological Anderson transition with quantum walks - Bagrets, Dmitry; Kim, Kun Woo; Barkhofen, Sonja; De, Syamsundar; Sperling, Jan; Silberhorn, Christine; Altland, Alexander; Micklitz, Tobias (Physical Review Research)

Split-ring polariton condensates as macroscopic two-level quantum systems - Xue, Yan; Chestnov, Igor; Sedov, Evgeny; Kiktenko, Evgeniy; Fedorov, Aleksey K.; Schumacher, Stefan; Ma, Xuekai; Kavokin, Alexey (Physical Review Research)

Spin Polarization, Electron–Phonon Coupling, and Zero-Phonon Line of the NV Center in 3C-SiC - Jurgen von Bardeleben, Hans; Cantin, Jean-Louis; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Adsorption and Reaction of PbPc on Hydrogenated Epitaxial Graphene - Slawig, Diana; Gruschwitz, Markus; Gerstmann, Uwe; Rauls, Eva; Tegenkamp, Christoph (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Adatom mediated adsorption of N‐heterocyclic carbenes on Cu(111) and Au(111) - Jain, Mitisha; Gerstmann, Uwe; Schmidt, Wolf Gero; Aldahhak, Hazem (Journal of Computational Chemistry)
Keywords: Computational Mathematics; General Chemistry

Neighboring Atom Collisions in Solid-State High Harmonic Generation - Zuo, Ruixin; Trautmann, Alexander; Wang, Guifang; Hannes, Wolf-Rüdiger; Yang, Shidong; Song, Xiaohong; Meier, Torsten; Ciappina, Marcelo; Duc, Huynh Thanh; Yang, Weifeng (Ultrafast Science)
High harmonic generation (HHG) from solids shows great application prospects in compact short-wavelength light sources and as a tool for imaging the dynamics in crystals with subnanometer spatial and attosecond temporal resolution. However, the underlying collision dynamics behind solid HHG is still intensively debated and no direct mapping relationship between the collision dynamics with band structure has been built. Here, we show that the electron and its associated hole can be elastically scattered by neighboring atoms when their wavelength approaches the atomic size. We reveal that the elastic scattering of electron/hole from neighboring atoms can dramatically influence the electron recombination with its left-behind hole, which turns out to be the fundamental reason for the anisotropic interband HHG observed recently in bulk crystals. Our findings link the electron/hole backward scattering with Van Hove singularities and forward scattering with critical lines in the band structure and thus build a clear mapping between the band structure and the harmonic spectrum. Our work provides a unifying picture for several seemingly unrelated experimental observations and theoretical predictions, including the anisotropic harmonic emission in MgO, the atomic-like recollision mechanism of solid HHG, and the delocalization of HHG in ZnO. This strongly improved understanding will pave the way for controlling the solid-state HHG and visualizing the structure-dependent electron dynamics in solids.

Low-field onset of Wannier-Stark localization in a polycrystalline hybrid organic inorganic perovskite - Berghoff, Daniel; Bühler, Johannes; Bonn, Mischa; Leitenstorfer, Alfred; Meier, Torsten; Kim, Heejae (Nature Communications)
Abstract Methylammonium lead iodide perovskite (MAPbI 3 ) is renowned for an impressive power conversion efficiency rise and cost-effective fabrication for photovoltaics. In this work, we demonstrate that polycrystalline MAPbI 3 s undergo drastic changes in optical properties at moderate field strengths with an ultrafast response time, via transient Wannier Stark localization. The distinct band structure of this material - the large lattice periodicity, the narrow electronic energy bandwidths, and the coincidence of these two along the same high-symmetry direction – enables relatively weak fields to bring this material into the Wannier Stark regime. Its polycrystalline nature is not detrimental to the optical switching performance of the material, since the least dispersive direction of the band structure dominates the contribution to the optical response, which favors low-cost fabrication. Together with the outstanding photophysical properties of MAPbI 3 , this finding highlights the great potential of this material in ultrafast light modulation and novel photonic applications.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Microscopic analysis of high harmonic generation in semiconductors with degenerate bands - Thong, Le Huu; Ngo, Cong; Duc, Huynh Thanh; Song, Xiaohong; Meier, Torsten (Physical Review B)

Electron polarons in lithium niobate: Charge localization, lattice deformation, and optical response - Schmidt, Falko; Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero; Schindlmayr, Arno (Crystals)
Lithium niobate (LiNbO3), a material frequently used in optical applications, hosts different kinds of polarons that significantly affect many of its physical properties. In this study, a variety of electron polarons, namely free, bound, and bipolarons, are analyzed using first-principles calculations. We perform a full structural optimization based on density-functional theory for selected intrinsic defects with special attention to the role of symmetry-breaking distortions that lower the total energy. The cations hosting the various polarons relax to a different degree, with a larger relaxation corresponding to a larger gap between the defect level and the conduction-band edge. The projected density of states reveals that the polaron states are formerly empty Nb 4d states lowered into the band gap. Optical absorption spectra are derived within the independent-particle approximation, corrected by the GW approximation that yields a wider band gap and by including excitonic effects within the Bethe-Salpeter equation. Comparing the calculated spectra with the density of states, we find that the defect peak observed in the optical absorption stems from transitions between the defect level and a continuum of empty Nb 4d states. Signatures of polarons are further analyzed in the reflectivity and other experimentally measurable optical coefficients.

Coherent and incoherent contribution of population dynamics of semiconductor exciton-polaritons - Meier, Torsten; Paul, Jagannath; Rose, Hendrik; Wahlstrand, Jared K; Bristow, Alan D (Frontiers in Optics)
Population/mixing-time-dependent two-dimensional coherent spectra are presented for exciton-polaritons in a microcavity. Theory based on dynamically-controlled truncation reveals coherent and incoherent contributions to the decay dynamics.